Endometrial metaplasias and reactive changes: a spectrum of altered differentiation. Issue 2 (1st December 2010) - Nicolae, Alina; Preda, Ovidiu; Nogales, Francisco F
Abstract : Endometrial metaplasias and changes (EMCs) are conditions frequently overlooked and misdiagnosed. The aim of this review is to update current issues and provide a classification with a practical clinicopathological approach. Hormonal or irritative stimuli are the main inducing factors of EMCs, although some metaplasias have a mutational origin. EMCs vary from reactive, degenerative lesions to those able to associate with malignancy or those having a preneoplastic potential. The most common types of EMCs are ciliated tubal metaplasia (CTM) and mucinous metaplasia (MM), which occur in simple and complex glands, and possibly these architectural changes hold the same prognostic significance as they do in hyperplastic endometrioid lesions. Immunohistochemically, CTM is positive for LhS28, bcl-2, PAX2 and p16 INK4A . Complex CTM is likely to be a precursor of ciliated endometrioid-type carcinomas. MMs should be evaluated architecturally, taking into account that their atypicality is minimal. The differentiation between complex MM and mucinous carcinoma may be extremely difficult. Surface complex, papillary MM in endometrial polyps can be considered as benign. Intestinal-type endometrial MM is rare and its presence should prompt further investigation of associated lesions in the endocervix. Endometrial squamous metaplasia (ESS) is often linked to chronic irritative situations. It should be differentiated from secondary involvement by a human papilomavirus-related cervical lesion. Morular metaplasia is a mutational phenomenon with a distinct phenotype that helps to differentiate it from ESS. Morules are benign, hormonally inert structures that are often markers of complex endometrioid glandular architecture, and they are associated with an attenuated malignancy. Endometrial reactive changes are commonly associated with desquamation or hormonal imbalance. The frequent, p16 INK4A positive, benign surface papillary syncytial change may be misdiagnosed, in some cases, as surface serous adenocarcinoma. Eosinophilic, oxyphilic, oncocytic and clear cell changes are non-specific. Rare stromal metaplasias have little clinical significance and should be differentiated from implanted fetal or embryonal tissues.